Forgiveness : a philosophical exploration - Griswold, Charles L., 1951- (New York : Cambridge University Press, 2007)
This is a comprehensive text on forgiveness in both its interpersonal and political contexts, as well as its relation to reconciliation
Forgiveness ancient and modern -- Pardon, excuse, and forgiveness in ancient philosophy : the standpoint of perfection -- Bishop Butler's seminal analysis -- Resentment -- Forgiveness -- Forgiveness at its best -- Forgiveness, revenge, and resentment -- Resentment and self-respect -- To be forgiven: changing your ways, contrition, and regret -- Forgiving: a change of heart, and seeing the offender and oneself in a new light -- The conditions of forgiveness: objections and replies -- Atonement and the payment or dismissal of a debt -- Forgiveness as a gift and unconditional forgiveness -- Praiseworthy conditional forgiveness -- Moral monsters, shared humanity, and sympathy -- Moral monsters -- Shared humanity and fallibility, compassion, and pity -- Sympathy -- The unforgivable and the unforgiven -- Forgiveness, narrative, and ideals -- Forgiveness, reconciliation, and friendship -- Imperfect forgiveness -- Ideal and non-ideal forgiveness: an inclusive or exclusive relation? --
Includes bibliographical references (pages 215-231) and index
Keywords: Forgiveness